Awareness Towards Jamu Classification in JABODETABEK Area - nur rahmah; runita rizkiyanti putri (Liaison Journal of Engineering, 2023)
Indonesia is endowed with natural resources especially medicinal plants. The medicinal plants have been used as the raw material of traditional medicine to treat and prevent various diseases long before modern pharmaceutical was introduced. The most popular Indonesian traditional medicine called as jamu. Jamu have been consumed by the ancestors and passed down from generation to next generation. The local society believed the health benefits after consuming jamu such as to maintain health and wellness and boosting immune system and the consumption of jamu significantly increased during covid-19 pandemic. There are three classification of traditional medicine which are jamu, standardized herbal medicine, and fitofarmaka. This study aimed to discuss the awareness towards jamu classification in Jabodetabek area. This studywas a quantitative research by distributing a questionnaire through social media that was filled by 309 respondents. Result showed that less than 20% of both male and female respondent aware different jamu classifications. The factors that make respondent do not know the jamu classification is the lack of information in the internet sources or news. Therefore, the role of the government, health workers, and herbalist are needed to socialize the information about traditional medicine directly. Keywords: Jamu, Herbal Medicine, Classification